Motives and pathways for joining outlaw motorcycle gangs - Voce, Isabella (Trends & issues in crime and criminal justice, 2024)
We analysed 39 interviews with former outlaw motorcycle gang (OMCG) members in Queensland to explore how and why they joined OMCGs. OMCG members were usually recruited through existing social networks. Screening was key to the recruitment process, and typically involved current and aspiring OMCG members getting to know one another and establishing rapport and trust. Recruitment was usually a lengthy process, supported by formal mechanisms including sponsorship by existing members and the enforcement of prospect or nominee periods. While a handful of more recent recruits were motivated by notoriety and profit, the brotherhood and camaraderie of affiliating with like-minded peers was the dominant motive for joining. Often this intersected with feelings of social isolation and disconnection from other family and peer networks. Findings highlight the importance of intervening with men early in their recruitment process, targeting high-risk settings for recruitment and reducing the attraction and visibility of OMCGs to prevent recruitment.